FACT SHEET ON AB 13 (T. FRIEDMAN): WORKPLACE SMOKING BAN (Tufts Archival Research Center, 2007)
Fact sheet in bill AB 13. Gives information on the health risks associated with secondhand smoke as support for the bill. Lists organizations that are in support of the bill, and